Building Your Brand: Analysis of Successful Oculoplastic Surgeons on Social Media. Issue 6 (November 2020) - Park, Sally S. E.; Akella, Sruti S.; Moon, Jee-Young; Zarrin, Bryan; Patel, Sheel; Doshi, Hiten; Barmettler, Anne
Abstract : Purpose: To determine the impact of social media content from oculoplastic surgeon-held accounts on public engagement. Methods : This study analyzed successful Instagram accounts (defined by >500 followers as of May 2019) held by American Society of Ophthalmic Plastic Reconstruction Surgery members. Each account's 20 most and 20 least successful posts (based on number of likes) were characterized by the post's subject, location, media type, and tag usage. Posts were then analyzed using a web-based application that calculates the engagement level of Instagram users with the selected post. Results : A total of 4, 812 posts were analyzed from 37 Instagram accounts. Of these American Society of Ophthalmic Plastic Reconstruction Surgery members, the majority were men (67.6%, n = 25) in private practice solely (70.3%, n = 26). Numerous post characteristics, like content and media type, impacted success in a statistically significant manner; for example, public engagement rose when featuring the posting doctor, especially when smiling and wearing a white coat. Meanwhile, posts featuring an office procedure had a negative effect. Formatting was also found to contribute to success. For example, photographs were preferred over videos, while multiple images were best presented sequentially as a carousel (with the viewer swiping through the series) rather than in a large collage. Use of tags (hashtags, accounts, and locations) were associated with increased engagement. Conclusions : Social media is an important communication and marketing tool, especially in esthetic fields like oculoplastics. Guidelines for success are presented in this study; content, location, subject, media type, and tags statistically significantly impact public engagement. The influence of social media is rapidly growing and can be strategically harnessed by oculoplastic surgeons to educate both patients and healthcare providers, collaborate with colleagues, and for referrals and marketing. Supplemental Digital Content is available in the text. Abstract : Supplemental Digital Content is available in the text.